2022
DOI: 10.1002/mabi.202100451
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation and Immunological Parameters of Polyurethane‐Based Tissue Adhesive in Arterial Microvascular Anastomoses—A Long‐Term In Vivo Study

Abstract: In microsurgical anastomosis, non‐synthetic fibrin‐based adhesives have predominantly shown superior properties to synthetic cyanoacrylates, but they have hardly any clinical application. This study aims to investigate the local and systemic effects of synthetically produced biodegradable adhesive VIVO when used in microsurgical anastomosis. VIVO is used in two different anastomosis procedures in the common carotid artery in a rat model: VIVO in addition to a temporary catheter (VIVO TC) and VIVO with a custom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Nevertheless, a major disadvantage of collagen sponges is that they are made of animal native type I and type III collagens [46], and these, like any xenogeneic preparation, pose an increased risk of allergic, immunologic, and even anaphylactic reactions [47]. In rat studies, VIVO showed sufficient hemostasis under moist conditions when applied in a sealing fashion to vascular anastomoses [20,24]. In the histologic evaluation, VIVO showed comparable thrombus formations when compared to extraction sockets treated with GSP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a major disadvantage of collagen sponges is that they are made of animal native type I and type III collagens [46], and these, like any xenogeneic preparation, pose an increased risk of allergic, immunologic, and even anaphylactic reactions [47]. In rat studies, VIVO showed sufficient hemostasis under moist conditions when applied in a sealing fashion to vascular anastomoses [20,24]. In the histologic evaluation, VIVO showed comparable thrombus formations when compared to extraction sockets treated with GSP.…”
Section: Discussionmentioning
confidence: 99%
“…The novel polyurethane-based tissue adhesive VIVO (Adhesys Medical GmbH, Aachen, Germany) is an innovative biodegradable adhesive that has demonstrated rapid and safe application [20]. It is an alternative to conventional hemostasis [21][22][23] with favorable tissue compatibility [24], as evidenced by good biocompatibility during the various degradation phases [23]. The authors hypothesized that the use of polyurethane-based VIVO leads to a decrease in postoperative bleeding under good wound healing conditions after dental removal under rivaroxaban therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene glycol (PEG) hydrogels, represented by FocalSeal and TissuGlu, boast adaptability and biocompatibility, making them valuable for the dynamic realm of vascular anastomosis [ 104 , 105 ]. Polyurethane-based adhesives add another dimension of choice in the anastomosis toolkit [ [106] , [107] , [108] ]. Furthermore, polysaccharide-based adhesives, derived from natural sugars, guarantee both biodegradability and biocompatibility, ensuring effective vascular seals with minimized inflammation [ [109] , [110] , [111] ].…”
Section: Sutureless Anastomotic Approaches Undergoing Developmentmentioning
confidence: 99%
“…A novel biodegradable polyurethane-based adhesive, VIVO, was introduced as an additional safety measure in surgical procedures [ [106] , [107] , [108] ]. Comprising an isocyanate-functionalized prepolymer and an amino-based curing agent, VIVO exhibited impressive adhesive strength on wet tissues.…”
Section: Sutureless Anastomotic Approaches Undergoing Developmentmentioning
confidence: 99%
See 1 more Smart Citation